The Relationship Between Knowledge Level and Attitude Toward the Use of Analgesic Drugs in the Community in East Medan - Tasia Dewi Cintoro; RR Sinta Irina (Sumatera Medical Journal, 2025)
Background: Pain, a common medical complaint, prompts many individuals to seek relief. Among the most frequently purchased drugs for self-medication are those from the analgesic-antipyretic group. The American Pain Society even designates pain as the 'fifth vital sign' due to its significance. Unfortunately, inadequate education provided by health professionals and a substantial number of untreated pain cases contribute to this situation. When used irrationally, analgesics can lead to various side effects, including stomach and intestinal disorders, hypersensitivity reactions, and damage to the kidneys and liver. Research from the Rational Use of Medicines in the ASEAN Region 2017 reveals that irrational drug use persists across all levels of health facilities in Indonesia. Objective: To investigate the relationship between analgesic knowledge and the utilization of analgesics in East Medan. Methods: This research constitutes an observational analytic study with a cross-sectional design. Respondents completed a questionnaire regarding their knowledge and usage of analgesics. Data were collected through consecutive sampling until 100 residents of East Medan were included. Subsequently, all the data were analyzed using Chi-Square analysis. Results: There was a relationship between analgesic knowledge and the utilization of analgesics (p=0.004). Conclusion: There exists a relationship between analgesic knowledge and the utilization of analgesics.